HET0016 inhibits neuronal pyroptosis in the immature brain post-TBI via the p38 MAPK signaling pathway - Xiaoli Chen; Ya‐Lei Ning; Bo Wang; Jun Qin; Changhong Li; Ruo‐Bing Gao; Zhihui Ma; Yuan‐Guo Zhou; Ping Li; Yan Zhao; Yan Peng; Xing Chen; et al. (2023)
Traumatic brain injury (TBI) is a serious health threat worldwide, especially for the younger demographic. Our previous study demonstrated that HET0016 (a specific inhibitor of 20-hydroxyeicosatetraenoic acid synthesis) can decrease the lesion volume in the immature brain post-TBI; however, its mechanism of action and its association with pyroptosis post-TBI are unclear. In this study, we established a controlled cortical impact (CCI) injury rat model (postnatal day 9–10) and observed that increased expression of indicators for pyroptosis, including NLR family pyrin domain containing 3 (NLRP3), caspase-1 and gasdermin D (GSDMD) proteins and interleukin (IL)-18/IL-1β mRNA during the acute phase of TBI, especially on post-injury day (PID) 1. Additionally, we found that caspase-1 was primarily expressed in the neurons and microglia. HET0016 (1 mg/kg/d, ip, 3 consecutive days since TBI) reduced the lesion volume; neuronal death; expression of NLRP3, caspase-1, and GSDMD; and expression of IL-18/IL-1β mRNA. Bioinformatics analysis suggested involvement of mitogen-activated protein kinase (MAPK) signaling pathway in the HET0016-mediated neuroprotective role against TBI in the immature brain. Western blot analysis revealed reduced expression of p-p38 MAPK and nuclear factor-kappa B (NF-κB) p65 in the neurons and microglia upon HET0016 treatment in TBI rats. In cultured primary cortical neurons subjected to oxygen-glucose deprivation/re-oxygenation (OGD) + (lipopolysaccharide) LPS, HET0016-induced the reduction of p-p38 MAPK, NLRP3, cleaved-caspase-1, GSDMD, IL-18, and IL-1β was reversed by co-treatment with p38 MAPK activator as well as NLRP3 agonist. Therefore, we conclude that pyroptosis is involved in neuronal death in the immature brains post-TBI and that HET0016 administration can alleviate neuronal pyroptosis possibly via inhibiting the phosphorylation of p38 MAPK.